PENGARUH APLIKASI HIDROGEL DAN KOMPOS TERHADAP RETENSI AIR DAN PERTUMBUHAN TANAMAN SORGUM PADA ULTISOL - Muhamad Slamet Nugroho; Sugeng Prijono; I Made Sudiana (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Ultisol has several constraints in the management and utilization for crop production such as erosion, easy leaching, low water retention, low cation exchange capacity and low nutrients. Provision of soil conditioner in the form of hydrogel and compost can increase water retention and improve some properties and nutrient content on the soil to increase plant growth. This study was conducted in a greenhouse of the Biology Research Center LIPI Cibinong, using a factorial randomized complete design with three replications in two experimental units, i.e. soil incubation and soil planted with Sorghum bicolor Super 2. Treatments tested consisted of a combination of hydrogel treatments with doses of 0,5 g kg-1, 1 g kg-1, 2 g kg-1, and 4 g kg-1 of hydrogels and compost treatmenst with dosesÂ  0 g kg-1, 30 g kg-1, and 60 g kg-1. The results showed that the combination of hydrogel and compost significantly affected soil characteristics and increased the growth of sorghum compared with control. However, interactionsÂ  between the treatment of hydrogels and compost were only observed for permanent wilting point, water content of field capacity and pore drainage. In general, the combination of hydrogel and compost treatment with the highest dose of H4K2 (4 g kg-1 hydrogels and compost 60 g kg-1) had the best effect on increasing water retention and sorghum plant growth on Ultisol.